Stories from the middle: Perceptions of the roles of curriculum development managers in a Maltese further education organization - NICHOLAS ZARB (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: In this case study, middle managers in a Maltese Further Education (FE) organization express their views on professionalism. The selected managers will play an academic and administrative role as Curriculum Development Managers (CDMs).Method: In this research, we used an instrumental case study approach guided by theory and interpreted through the lens of critical realism. In this case study, ten CDMs and two SMT members participated in semi structured interviews to discuss their respective roles, skills, values, management education, and challenges.Findings: Participants viewed their roles as administrative and managerial, with personnel management and dealing with unreasonable bureaucratic structures cited as the greatest difficulties. Efficiency, organization, fairness, and discipline were identified as the most important qualities for success in their position. Few respondents had formal management training, but nearly everyone agreed that internal training was necessary.Implications/Novel Contribution: This paper demonstrates the potential of case studies for illuminating the lived experiences of individuals within organizations and comparing those accounts to those found in other parts of the world. Despite the study’s limitations, such as its relatively small sample size, it may be worthwhile to broaden the scope of this investigation to encompass additional FE institutions.